A LITERARY MITHOLOGY STUDY ON THE STORY OF THE BAPAK BIOLOGI SOEKARNO-BILOGICAL FATHER OF SOEKARNO - S. Samsuddin (Journal of Indonesian Language Education and Literary, 2017)
The story of Bapak Biologi Soekarno (bilogical father of Soekarno) is a story that developed in the community of Butonese. This story contains the existence of Soekarno who was born from the descendants of the nobleman of Buton, La Ode Muhammad Idris. This story is certainly controversial with the historical record of the Indonesian nation who recognizes Raden Soekemi Sosrodihardjo as the father of Soekarno. This controversy is very strong. Each maintains a belief that is assumed to be true. This controversy can be decomposed by restoring the essence of myth as a narrative story. Myths are seen in various dimensions, such as (1) factual, (2) scientific, (3) imagination, and (4) spiritual. These four dimensions then give rise to the four truths in the narrative story, such as (1) factual truth, (2) scientific truth, (3) the truth of the imagination, and (4) spiritual truth. Referring to the nature of the narrative story and its truths, the controversy of Biological Father of Soekarno is not necessarily the case. Both have elements of truth, either factually, scientifically, imaginatively, or spiritually.